2005
DOI: 10.1111/j.1471-0528.2005.00708.x
|View full text |Cite
|
Sign up to set email alerts
|

CASE REPORT: Maternal death after intrapartum saline amnioinfusion—report of two cases

Abstract: Case reportIntrapartum transcervical amnioinfusion is an accepted therapeutic measure in the presence of variable decelerations with or without meconium-stained amniotic fluid. 1 Widely varying protocols are being used and have been thought to be safe.2 Amniotic fluid embolism and or pulmonary oedema in patients undergoing amnioinfusion have been described in six cases reports although no causal link has been established. We report two fatal cases of probable amniotic fluid embolism after saline amnioinfusion.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
1
1

Year Published

2007
2007
2014
2014

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 10 publications
0
11
1
1
Order By: Relevance
“…Complications including uterine overdistension and hypertonia, uterine rupture in association with previous uterine scar, fetal heart rate abnormality, umbilical cord prolapse, and chorioamnionitis have been reported. [47][48][49][50] In summary, our main meta-analysis that is based on trials with high-quality scores suggests no evidence of effectiveness of AI in the reduction of the risk of MAS in clinical settings with standard peripartum surveillance. However, in settings with limited peripartum surveillance, AI appeared to reduce the risk of MAS.…”
Section: Discussionmentioning
confidence: 99%
“…Complications including uterine overdistension and hypertonia, uterine rupture in association with previous uterine scar, fetal heart rate abnormality, umbilical cord prolapse, and chorioamnionitis have been reported. [47][48][49][50] In summary, our main meta-analysis that is based on trials with high-quality scores suggests no evidence of effectiveness of AI in the reduction of the risk of MAS in clinical settings with standard peripartum surveillance. However, in settings with limited peripartum surveillance, AI appeared to reduce the risk of MAS.…”
Section: Discussionmentioning
confidence: 99%
“…Complications including uterine overdistension and hypertonia, uterine rupture in association with previous uterine scar, FHR abnormality, umbilical cord prolapse and chorioamnionitis have been reported. [56][57][58][59] Four cases of maternal deaths have been reported associated with the AI. 58,59 Several authors have reported the occurrence of excessive uterine contractions or unusually rapid labor progress related to AI.…”
Section: Pathophysiology and Risk Factorsmentioning
confidence: 99%
“…[56][57][58][59] Four cases of maternal deaths have been reported associated with the AI. 58,59 Several authors have reported the occurrence of excessive uterine contractions or unusually rapid labor progress related to AI. In the AI group of Fraser et al's 55 trial, 10 women (1.1%) experienced bleeding, and in 63 (6.9%) women, hypertonicity, hydramnios or uterine overdistension was diagnosed during the procedure whereas the incidence of other maternal complications were comparable between AI and control groups.…”
Section: Pathophysiology and Risk Factorsmentioning
confidence: 99%
“…Kochsalzlösung zur Mekoniumaspirationsprophylaxe wurden mehrere Fälle mit Fruchtwasserembolie beschrieben [12]. Ein stumpfes Bauchtrauma kann ebenfalls zur Fruchtwasserembolie führen [13].…”
Section: üBersicht Und Darstellung Von Fällen Mit Gutem Outcomeunclassified